The The European Union NATO in the face of China's increase in power in Africa and the Mediterranean: Analysis in light of the NATO Strategic Concept 2022 (Journal of the Spanish Institute for Strategic Studies, 2023)
The increase in power of China feeds the reticence of the Western powers. The latter, led by the United States, are aware that China is rebuilding the international order in their favor, to the detriment of their interests. The growing presence of China in the perimeters of strategic interest of the Western powers consolidates these misgivings. In this sense, the Mediterranean and Africa have experienced in recent years a constant increase in the power of China's soft and hard power. An expansion of a mainly economic and commercial nature but also strategic and political. Rivalry and competition between international powers in these regions could unbalance powers and exacerbate disputes. This reality will cause the countries of these regions - like the countries of Asia Pacific - to find themselves facing growing challenges in their foreign policies such; the difficulty of freely developing their relationships with third parties, the obligation to align with one ally and sacrifice another, and the choice between economic interests or strategic interests.
Keywords: China; USA; EU; NATO; Africa; Mediterranean